A test of the tripartite influence model of disordered eating among men. (March 2021) - Schaefer, Lauren M.; Rodgers, Rachel F.; Thompson, J. Kevin; Griffiths, Scott
Highlights: Results provide support for the Tripartite Influence Model among men. Thinness/muscularity pressures predicted thin/muscular internalization and comparisons. Thin/muscular internalization and comparisons predicted disordered eating. Abstract: Studies of the Tripartite Influence Model conducted with female samples suggest that thinness-oriented pressures, internalization, and appearance comparisons may be risk factors for disordered eating. However, limited work has investigated this model among men utilizing measures specifically designed to assess both muscularity- and thinness-oriented processes, which characterize male body image concerns. To address this gap, the current study examined the Tripartite Influence Model of disordered eating among men using a battery of such measures. A convenience sample of 265 male undergraduates completed validated, self-report measures of disordered eating, muscularity- and thinness-oriented appearance pressures, internalization, and appearance comparisons. Path analyses supported a slightly modified version of the Tripartite Influence Model, indicating direct and indirect paths from sociocultural pressures to disordered eating via internalization and appearance comparisons. These results provide support for a version of the Tripartite Influence Model among men. Specifically, muscularity- and thinness-oriented pressures appear to be related to disordered eating among college men via indirect pathways involving thin internalization, muscular internalization, and appearance comparisons. Future work is needed, however, to examine whether the model would generalize to muscularity-oriented disordered eating.